Valgus mechanism inducing a unique “terrible triad injury” pattern in the elbow: a detailed clinical and surgical analysis - Wang, Yanmao; Yu, Shiyang; Ding, Jian (Frontiers in Surgery, 2025)
AimsThe most accepted theory to explain the mechanism of “terrible triad injury (TTI)” of the elbow was proposed by O’Driscoll, describing it as a result of rotatory instability. However, a small subset of TTI cases appears to follow a different mechanism based on their clinical presentation. The aim of this study was to describe this injury pattern in detail and to suggest a treatment strategy that may lead to improved outcomes.Patients and methodsCases of elbow dislocation treated between July 2017 and July 2019 were analyzed and identified as the valgus-type TTI through radiographs and surgical findings. Fractures and associated injuries were evaluated and compared with non-valgus TTIs. The current treatment method and prognosis were reviewed to formulate a preliminary feasible treatment plan.ResultsOf 313 patients, 13 were diagnosed with valgus-type TTI. The mean age of these patients was 45.8 years, with the majority (84.6%) sustaining injury from low-energy trauma. No neurovascular injuries were observed. Three patients were treated non-operatively, while 10 underwent surgical treatment. In these 10 cases, coronoid avulsion of the medial collateral ligament (MCL) and continuity of the lateral ulnar collateral ligament were confirmed. Elbow function had a Mayo Elbow Performance Score of 98 and a Quick-Disabilities of the Arm, Shoulder, and Hand score of 6.38. No re-interventions were required after the initial treatment. Of the 13 patients, eight showed non-union of the MCL avulsion, though this did not affect stability. The remaining patients achieved radiographic union at an average of 10.7 weeks.ConclusionValgus-type TTI is a rare and distinct variant of TTI, but is less severe than the classic form. Surgeons should be aware of its associated injuries. The treatment strategy described here allows for targeted management of the injury's individual components, potentially reducing the risk of treatment failure.